Floating matrix tablets of atenolol: Formulation and in vitro evaluation - Havaldar, VD; Kulkarni, AS; Dias, RJ; Aloorkar, NH; Mali, KK (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of the study was to prolong the gastric residence time of atenolol by designing its floating tablets and to study the influence of different polymers on its release rate. Nine formulations of atenolol containing varying concentrations of polymers were designed by optimization. The floating matrix tablets of atenolol were prepared by direct compression method. The prepared tablets were evaluated for physicochemical parameters such as hardness, floating properties (floating lag time, floating time and matrix integrity), swelling studiesÂ and drug content. The physicochemical parameters of formulated tablets were found to be within normal range. A significant difference in drug release (P , 0.0001) and floating lag time (P , 0.005) at 0.5, one, four and eight hours were observed. The floating lag time of all the formulations was within the prescribed limit (,10 minutes). All the formulations showed good matrix integrity and retarded the release of drug for eight hours. The release pattern of atenolol was fitted to different models based on coefficient of correlation (r). All the formulations, except F2, F3 and F6 showed Korsemeyer-Peppas model as the best fit model. Formulation F2 and F3 showed first order model while F6 showed zero order model. Diffusion exponent (n) value was found in the range of 0.52-0.99 indicating diffusion as a release mechanism. The swelling studies of all the formulations showed that formulations containing Xanthan gum has higher swelling indices than HPMC K100M and HPMC K4M. It can be concluded that formulations with higher swelling indices retarded the release of drugs more than those with lower swelling indices.